2017
DOI: 10.1111/anae.14159
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optimal programmed intermittent epidural bolus volume of bupivacaine 0.0625% with fentanyl 2 μg.ml−1 at a fixed interval of forty minutes: a biased coin up‐and‐down sequential allocation trial

Abstract: The optimum time interval for 10 ml boluses of bupivacaine 0.0625% + fentanyl 2 μg.ml as part of a programmed intermittent epidural bolus regimen has been found to be 40 min. This regimen was shown to be effective without the use of supplementary patient-controlled epidural analgesia boluses in 90% of women during the first stage of labour, although with a rate of sensory block to ice above T6 in 34% of women. We aimed to determine the optimum programmed intermittent epidural bolus volume at a 40 min interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 15 publications
1
28
2
Order By: Relevance
“…Since all three groups had an equal hourly dose of bupivacaine (12.5 mg), our results suggest that higher PIEB volumes are necessary for optimal analgesia. The results of two up-and-down studies using bupivacaine 0.0625% with fentanyl 2 μg/ml show that the optimal PIEB dosing interval and volume are 40 min and 11 ml, respectively [17,18]. The optimal hourly bupivacaine dose from the up-and-down studies is 10.3 mg, which is lower than our hourly bupivacaine dose.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Since all three groups had an equal hourly dose of bupivacaine (12.5 mg), our results suggest that higher PIEB volumes are necessary for optimal analgesia. The results of two up-and-down studies using bupivacaine 0.0625% with fentanyl 2 μg/ml show that the optimal PIEB dosing interval and volume are 40 min and 11 ml, respectively [17,18]. The optimal hourly bupivacaine dose from the up-and-down studies is 10.3 mg, which is lower than our hourly bupivacaine dose.…”
Section: Discussionmentioning
confidence: 80%
“…One explanation is that our study uses a relatively high hourly bupivacaine dose of 12.5 mg/h. Recent reports have demonstrated that lower hourly bupivacaine doses (7.5–10.3 mg) are effective when administered with higher volume PIEB [1,18,20]. These findings suggest that higher volume, lower concentration PIEB regimens may be ideal.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the optimal PIEB mode has yet to be determined with regard to programmed bolus volume, time interval, local anesthetic, or its concentration [ 8 , 12 , 13 ]. Thus, we chose a pragmatic approach using our standard settings for epidural catheters of 6 mL/h − 1 for the CEI group and the same volume for the PIEB in the PIEB group.…”
Section: Discussionmentioning
confidence: 99%
“…In the BCD, volume assignment is carried out in a sequential and interactive method, which avoids that patients are randomized to doses with toxicity risk and seeks to concentrate treatments around the suitable doses. The BCD design has been applied in anaesthesia dose‐finding studies concerning inhalation agents 21 and LAs for neuraxial analgesia 22 and PNB 23‐26 . This trial has, in compliance with aforementioned review and Tran et al's dose‐finding study, 23 applied the BCD to determine the minimal effective volume (MEV 90 ) for the TQL block.…”
Section: Introductionmentioning
confidence: 99%